THE RESPONSE OF ISLAMIC EDUCATION TO THE ADVANCEMENT OF SCIENCE IN THE COVID-19 PANDEMIC ERA IN THE ISLAMIC BOARDING SCHOOLS - Mansir, Firman (AULADUNA: Jurnal Pendidikan Dasar Islam, 2021)
Abstract This study discussed that Islamic boarding schools as educational institutions responded to Covid 19 pandemic era through their educational system. This study aimed to examine how Islamic educational institutions responded to the advancement of science in the current Covid-19 era. The method used was the library research method with a qualitative approach by excavating, discovering, reading, explaining, and conveying implicitly or explicitly to literature from the data. The source data came from articles, journals, and books related to Islamic education, Islamic boarding schools, and the response of Islamic education to the Covid-19 pandemic. In analyzing the data, the researcher used data descriptive and content analyses. The findings indicated that Islamic boarding schools applied online learning during the Covid-19 Pandemic era. Therefore, Islamic boarding schools responded by using science technology in the learning process by developing lesson plans based on the current situation. Abstrak Penelitian ini membahas pondok pesantren sebagai lembaga pendidikan yang merespon pandemi Covid-19 melalui sistem pendidikannya. Penelitian ini bertujuan untuk mengkaji bagaimana lembaga pendidikan Islam menyikapi kemajuan ilmu pengetahuan di era Covid-19 saat ini. Metode yang digunakan adalah metode penelitian kepustakaan dengan pendekatan kualitatif dengan menggali, menemukan, membaca, menjelaskan, dan menyampaikan secara implisit atau eksplisit ke literatur dari data. Sumber data berasal dari artikel, jurnal, dan buku terkait pendidikan Islam, pesantren, dan respon pendidikan Islam terhadap pandemi Covid-19. Dalam menganalisis data, peneliti menggunakan deskriptif data dan analisis isi. Temuan menunjukkan bahwa pesantren menerapkan pembelajaran online selama era Pandemi Covid-19. Oleh karena itu, pondok pesantren meresponnya dengan menggunakan iptek dalam proses pembelajarannya dengan mengembangkan RPP berdasarkan situasi saat ini.